STRUCTURE ANXIETY STATES AMONG PATIENTS PNEUMOCONIOSIS - Vasyakina, L.A. (World of Medicine and Biology, 2012)
The structure, dynamics and clinical-psychological manifestations of pneumoconiosis patients with anxiety states were investigated from the position of systemic approach. The psychopathological disturbance’s features and personality’s peculiarities in studied patients were research. The anxiety state’s promoting development factors on a hum noise of somatic disease and patopsychology mechanisms of mutual burdening are revealed.
Keywords: pneumoconiosis; anxiety states; psychopathology disorders; patopsychology